Implementation of Education Supervision at Binjai MTSN School - Inom Nasution; Alwi Shihab Syah Harahap; Ilham Muhammad Fajar; Bella Bunda; Yunita Aisyah; Putri Feby Aulia (Edumaspul: Jurnal Pendidikan, 2022)
Supervision is a process that is often carried out in every educational institution. In this case, a research process was carried out at MTsN Binjai with the aim of seeing how the process of implementing supervision carried out by the head of MTSN Binjai on teachers. The methodology used in this study was descriptive qualitative research by conducting a process of observation and interviews at MTsN Binjai. . The results of the research process said that the supervision implementation process carried out by the head of MTSN Binjai was carried out well in accordance with established procedures. In addition, the head of MTSN Binjai also has a firmness in carrying out an implementation of supervision of teachers so that teachers can improve their abilities and performance in the teaching and learning process.